Globalization of Monitoring Practices: The Case of American Influences on the Dismissal Risk of European CEOs - Lars Oxelheim; Trond Randoy (Research Institute of Industrial Economics (IFN), 2013)
This study examines globalization of monitoring practices by focusing on how American (U.S.) influences on European firms impact the dismissal risk for these firms' CEOs. Specifically, we argue that the stronger short term orientation of the American corporate governance system increase the dismissal performance sensitivity faced by European CEOs, indirectly and directly. The former materializes via European firms cross-listing on U.S. exchanges, the latter results from European firms hiring U.S. independent board members. Both influences are expected to result in increased dismissal performance sensitivity. Based on data from the 250 largest European publicly traded firms we find a significant increase in the dismissal sensitivity of poorly performing companies with American board members and a support for migration of American executive pay practice. However, no significant increase in dismissal performance sensitivity was identified from U.S. cross-listing. In line with our agency theory based prediction, this indicates an institutional contagion driven by the presence of U.S. board members on European corporate boards. To policy makers the message is that internationalization of boards should not be banned or restricted, since it provides owners with more options to influence the corporate governance of the firm.
Keywords: G15; G18; G32; M14; M16; M52; 330; Executive pay; CEO dismissal; Performance sensitivity; Foreign board membership